Immigrants from the Crimea in Russia: Employment and Legal Status » - Andrey Belyakov (Золотоордынское обозрение)
The author is attempting to summarize all available information on the Crimean immigrants in the Russian state of the 15th–17th centuries. The article examines immigration processes of the Chinggisids: both the Gerays as well as other branches’ representatives, tribal noblemen and the “ordinary” Tatars. The author offers the following periodization of migration: 1) the last quarter of the 15th century – the 1530s; 2) the 1580s – early 17th century; 3) period after the completion of the Time of Troubles. According to the conclusions of the author, compared with migrants from other areas immigrants from the Crimean Khanate more easily integrated into the serving class of the local population and successfully maintained and expanded their “privileges”. At the same time, taking into account the specific nature of available sources, our knowledge is limited almost exclusively on the upper strata of the Crimean immigrants. Surviving documents contain very fragmentary information on immigrants who had inferior status in the social hierarchy compared to the Chinggisids or representatives of the clan aristocracy.